Epirubicin and gait apraxia: a real-world data analysis of the FDA Adverse Event Reporting System database - Wang, Wei; Guan, Xin; Wang, Shuang; Shi, Lipeng; Zhu, Yanfei; Hua, Pengbo; Guo, Qiang; Wang, Jingqi (Frontiers in Pharmacology, 2023)
Epirubicin is widely used to treat many malignancies and has good efficacy and tolerability. However, investigations on adverse events (AEs) using real-world information are limited. We extracted epirubicin-related reports submitted between the first quarters of 2014 and 2023 from the FAERS database. Four algorithms were used to evaluate whether there was a significant correlation between the epirubicin and AEs.After deduplication, 3919 cases were extracted. Among the 3919 cases, we identified 1472 adverse events (AEs), of which 253 were found to be adverse drug reactions (ADRs) associated with epirubicin. We analysed the occurrence of epirubicin-induced ADRs in 23 organ systems. Several expected ADRs were observed in accordance with the instructions, such as cardiac perfusion defects, endocardial fibrosis, and postembolization syndrome. Moreover, unexpected significant ADRs related to nervous system and hepatobiliary disorders were found at the system organ class (SOC) level, suggesting that there are potential adverse effects that have not been listed in the drug instructions. Our study identified unexpected and significant ADRs related to epirubicin, providing new perspectives on the clinical use of epirubicin.